High photocurrent generation by photosystem I on artificial interfaces composed of π-system-modified graphene1. Issue 23 (21st June 2015) - Feifel, S. C.; Stieger, K. R.; Lokstein, H.; Lux, H.; Lisdat, F.
<x xml:space="preserve">Abstract</x> We report on the development of graphene-nanobiohybrid light-harvesting electrodes consisting of photosystem I and π-system modified graphene electrodes.